Arsitektur Metafora Pada Perancangan Museum Tsunami di Pangandaran - WIDYANDINI, WITA; MAULANA, FARYD ACHMAD; NURSRUWENING, YOHANA (ReTII, 2021)
The Pangandaran Earthquake and Tsunami on July 17, 2006 was an unforgettable moment. To commemorate this moment, Pangandaran Tsunami Museum was designed.as a historical monument, an education and recreation center in Pangandaran. The approach to the architectural theme at the Pangandaran Tsunami Museum is the application of the metaphor architecture. The research methodology used is the qualitative method, with observation, interview, and dokumentation as the data collection technique. The research results are 1) Pangandaran Tsunami Museum uses an analogy like a sea wave which is based on the idea of ​​the tsunami incident, 2) The application of the metaphor architecture can be seen from the facade, floor plans, colors, ceiling patterns, and interior of Pangandaran Tsunami Museum.